2004
DOI: 10.1089/109287504322746776
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Cesium Sorption in Calcined Kaolin Packed Beds

Abstract: This study investigated the use of calcined kaolin particles in the size range of 300-400 mm as cesium capturing sorbents at high temperatures. Sorption tests by passing CsCl-carrying flue gas through the packed bed of calcined porous kaolin particles were performed over a temperature range of 973-1173 K and a CsCl partial pressure of 7.4-11.1 Pa. The observed structural change of the sorbent mineral at the stage of sorption revealed the characteristics of an irreversible chemical reaction as a major cesium ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Kaolinite also has the advantage that it is compatible with subsequent vitrification and cement processes. Yang et al (40) performed sorption experiments by passing Cs-laden flue gas through a packed bed of kaolin particles and found the chemical reaction at the kaolin surface controlled the overall reaction rates. Crosley and Kedl (41) performed a proof of concept experiment using a thermogravimetric analyzer and reported that silica was an effective sorbent for cesium.…”
Section: Introductionmentioning
confidence: 99%
“…Kaolinite also has the advantage that it is compatible with subsequent vitrification and cement processes. Yang et al (40) performed sorption experiments by passing Cs-laden flue gas through a packed bed of kaolin particles and found the chemical reaction at the kaolin surface controlled the overall reaction rates. Crosley and Kedl (41) performed a proof of concept experiment using a thermogravimetric analyzer and reported that silica was an effective sorbent for cesium.…”
Section: Introductionmentioning
confidence: 99%
“…Kaolinite also has the advantages that it is compatible with subsequent vitrification and cement processes. Yang et al (40) performed sorption experiments by passing Cs-laden flue gas through a packed bed of kaolin particles and found the chemical reaction at the kaolin surface controlled the overall reaction rates.…”
Section: Sorbent Technologymentioning
confidence: 99%